3. The Effect of Audio Recording for Playback Experiment to the Alteration of Orangutan’s Territorial Behavior - Rahmat Nazif; Gholib Gholib; Erdiansyah Rahmi; Arman Sayuti; Triva Murtina Lubis; Ummu Balqis (Jurnal Medika Veterinaria, 2018)
The aim of this study was to find an alternative method to prevent the conflict between the orangutan and human with the utilization of audio recording as biofence. The location of this study was in Leuser National Park on Bukit Lawang, Langkat, North Sumatra using 16 orangutans as the subject of this study. The method used in this study was a simulation and playback experiment which were using long call, spontaneous call, predator voice, and siren sound in the audio recording of non-alpha orangutans. The respond was observed using binocular and recorded using camera recorder. The data obtained were analyzed using Krustal Wallist test. The result showed that 87% of orangutan showed an interest in the attractor, on the other hand, 13% showed disinterest to the attractor. The facial expression shown by orangutan was fear, submission, aggression, and worry. The statistical analyzing result showed that long call and the spontaneous call was very significant (P0.01), while the predator and siren voice were insignificant (P0.05). The result can be concluded that long call and spontaneous calls showing the effective result to the alteration of territorial behavior on orangutan and have a potential as a biofence that is used as an alternative method to prevent the conflict between orangutan and human.